Modification de la technique de pédalage après un entraînement basé sur le feedback des forces appliquées sur les pédales - Mornieux, G.; Stapelfeldt, B. (Science et motricité, 2012)
The aim of the study was to investigate the influence of a training form leading to an active pull-up action on the pedal during the upstroke on both the pedaling technique and the cycling performance. After a four weeks training, cyclists applied a significant higher effective force during upstroke while generating a lower effective force during downstroke (at a 300 watts level). However, such changes in the pedaling technique did not influence the performance measured during a maximal incremental cycling test. Therefore, even if an active pull-up action on the pedal during upstroke seems to present a mechanical advantage, the benefit in terms of cycling performance remains to be demonstrated.